Analysis of parallel trade of pharmaceuticals in Poland and its impact on public health - Baran-Lewandowska, Izabela; Hermanowski, Tomasz (Polish Journal of Public Health, 2009)
Introduction. Easy access to pharmaceuticals plays a very important role in public health improvement. Especially in times of global crisis it is amazingly important to look for cheaper sources of medicines. Parallel import (PI) can bring an easy solution to this social need. PI of pharmaceuticals in Poland has been possible since Poland became an EU member. However, until now no comprehensive, scientific paper about PI in Poland has not been published yet. Objective. The objective of the present paper was to analyse the PI of pharmaceuticals in Poland in order to determine the calculation model for direct and indirect savings as a consequence of PI. Materials and methods. Thorough literature review and analysis of information published by The Polish Office for Registration of Medical Products, Medical Devices and Biocidal Products and data owned by IMS Health. Results. Till June 2009 the PI licences have been granted for 445 medicines in Poland for 18 parallel traders. Parallel imported products in Poland are mainly exported from Greece, the Czech Republic, France and, on average, they are cheaper by about 10%-60% than products from manufacturers in Poland. The value of sales, on the level of ex-factory price, from PI was PLN 82 million in 2008. Based on analysis performed, a methodology has been developed which will be used for calculation of savings from PI in Poland divided into public payer and patients. Conclusion. Importance of PI in Poland has increased consequently during the last few years and in the next years further growth of its market share is expected. Detailed calculation of savings resulting from this phenomena will be conducted in cooperation with European experts in the discussed area – University of Southern Denmark. Obtained results can be used in order to convince Polish decisionmakers that PI could be a source of substantial savings and new possibilities for public health and that it is necessary to implement appropriate directives supporting PI.